Pengendalian Limbah Cair Dan Dampak Pengaruh Limbah PT. Pabrik Es Siantar - Manres Nababan; Dian G. Purba; Stepan H Purba; Rafael Siregar; Muhammad Fauzi; Roni Agung Hasibuan; Rizki Sahertian; Jun Kifran Manik; Yosi Irawelda Saragih; Monika Siallagan; Ahmad Tarez Azhadi (Jurnal Mahasiswa Kreatif, 2024)
Established since 1916, PT. Pabrik Es Siantar is the oldest factory of Pematangsiantar. This study is aimed to determine what strategy are used by PT. Pabrik Es Siantar in maintaining the existence of ‘Cap Badak’ products; to know the strategy implementation, evaluation; and also its obstacles. Afterwards, this study analyzes the alternative strategy that possibly recommended to PT. Pabrik Es Siantar for supporting the existing strategy. The research method used is descriptive-qualitative, using case study. Data were collected by interviews, observation, and documentation. Data analysis techniques used were qualitative-descriptive analysis of Miles and Huberman and also SWOT Analysis using SWOT Matrix, IFE Matrix, EFE Matrix, and then matching the alternative strategies obtained on SWOT Diagram. The results showed that in maintaining the existence of Cap Badak products, PT. Pabrik Es Siantar uses Defense Strategy. The strategy implementation and evaluation has been done properly without changing any standards. The obstacles is they still using their conventional machines because the owner does not intend to regenerate the machines, and the production becomes less and hampered because many bottles are not returned to the factory yet. Furthermore, based on IFE Matrix, EFE Matrix, and SWOT Diagram, the results showed that PT. Pabrik Es Siantar is in Quadrant I, where the company’s position is very profitable and supports aggressive strategies. Based on SWOT Matrix Analysis, PT. Pabrik Es Siantar is recommended to launch Cap Badak products in plastic bottle packaging immediately, do promotion after regenerating machines, educate consumers about the importance of returning bottles on time, purchase orders bottles more often, and change the family management system into a more professional system.